Anticancer Potential of Ethanolic Extract Artocarpus heterophyllus Lam. Leaves against Human Colon Cancer WiDr Cell Line - Mutiyani, Novita; Nuriliani, Ardaning (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Jackfruit (Artocarpus heterophyllus Lam.) is a plant contains various compounds that has potential as anticancer drugs. Secondary metabolites of jackfruit leaves are flavonoids, alkaloids, tannins, triterpenoids, and saponins. A typical flavonoid compound group in the Artocarpus genus, namely artocarpin, is able to kill cancer cells through apoptosis. Not many have conducted cytotoxicity research and apoptosis induction of ethanolic extracts from jackfruit leaves, especially against WiDr colon cancer cells. Therefore, this study aims to study the cytotoxic effects and apoptosis induction of ethanolic extracts of jackfruit leaves against WiDr colon cancer cells. The research was conducted by cytotoxicity test using the MTT assay. Apoptosis test was done using double staining method with AO/PI dye. The treatment was conducted at various concentrations of ethanolic extract of jackfruit leaves, doxorubicin as positive control, and DMSO as solvent control. The data were analyzed by one way ANOVA (p â‰¤ 0.05) and continued using Tukey HSD Post Hoc test. The results showed that the ethanolic extract of jackfruit leaves was not toxic to WiDr cells with an IC50 740.43 Î¼g/mL, but could significantly reduce cell viability at a concentration of 500 Î¼g/mL. The ethanolic extract of jackfruit leaves could also induce apoptotic cell death at a concentration of 500 Î¼g/mL. Based on these results, ethanolic extract of jackfruit leaves has little potential to be developed as an anticancer drug.